Polskie biblioteki i problemy polskiego bibliotekarstwa w niemieckim piśmiennictwie fachowym - Kessler, Wolfgang (Biblioteka Uniwersytecka w Poznaniu, 2014)
Czasopisma bibliotekoznawcze nie odgrywają znaczącej roli w niemieckim bibliotekarstwie, jednak dość wiernie odzwierciedlają najważniejsze zagadnienia współczesnego bibliotekarstwa niemieckiego. Wybór tematów, jakie pojawiają się w ogólnokrajowych czasopismach fachowych, jest bardzo bogaty i wewnętrznie zróżnicowany: budownictwo i technika biblioteczna, katalogowanie, przetwarzanie danych, automatyzacja, szeroki dostęp do wszechstronnej informacji, a obok tego – przyjazne podejście do użytkowników, wszechstronne zaspokajanie ich potrzeb, kształcenie i doskonalenie umiejętności bibliotekarzy. Marginalnie i niesystematycznie ukazują się teksty dotyczące problemów współczesnego bibliotekarstwa zagranicznego, nie wyłączając bibliotekarstwa polskiego. Znajdziemy natomiast w piśmiennictwie niemieckim informacje na temat dziejów polskiej książki i bibliotek, zwłaszcza gdy chodzi o wczesne lata nowożytne. Dla niemieckich germanistów szczególnie interesujące są historyczne księgozbiory niemieckie w Europie Środkowo-Wschodniej.

Library professional journals in Germany do not have a significant impact on the scientific community within their own areas of interest, though articles published in them reflect quite accurately the most important issues of modern German librarianship. The range of subjects that appear in all-German professional publications is vast and diversified and covers the following: library architecture and technology, cataloguing data processing, automation, wide access to comprehensive information, as well as issues related to promoting friendly attitude towards users, presenting all-round packages of services for users, and discuss education and professional training for librarians. Articles related to problems of modern librarianship from the international perspective, including those related to Polish librarianship, are scarce and marginal. Notwithstanding, publications on the history of books and libraries in Poland, in particular those that relate to early modern era. do get coverage in library periodicals and are published in Germany more often. German specialists are particularly interested in historical German book collections currently held in Central and Eastern Europe.
Polish libraries and problems of contemporary polish librarianship in german professional periodicals
Keywords: Germany; Niemcy; library publications; piśmiennictwo bibliotekarskie; library periodicals; czasopisma bibliotekarskie; Polish librarianship; polskie bibliotekarstwo